Using metacognitive e-modules on cell cycle: Exploring students' conception and self-efficacy - Dacumos, Joyce Ann R. (Animo Repository, 2022)
The COVID-19 pandemic has changed various aspects of the community including the teaching and learning process. Several delivery methods have recently emerged as a counteraction to the effects of the pandemic on education. One popular modality is online learning or e-learning whereby students learn in a fully virtual environment. In this new setup where teachers are no longer in the same space as the students, utilization of metacognitive strategies and self-regulated processes among online learners is much needed. In this action research, the development and the utilization of e-modules with embedded metacognitive learning activities to enhance the conceptual understanding and self-efficacy beliefs of Grade 12 biology learners on the topic of cell cycle were investigated. Participants were composed of eighty-eight (88) learners from three grade 12 General Biology classes of Holy Angel University. Cell cycle concept tests and online learning self-efficacy scale (OLSES) were administered as pre-test and post-test. Likewise, data from the results of the metacognitive e-modules observation notes, assessment survey, interview protocol, assessment tools, responses to metacognitive prompts, and reflective journal entries were utilized for data triangulation. Results revealed that the metacognitive e-modules (MEMs) were well-developed in terms of content, usability, and potential effectiveness as a teaching tool. The processes of regulation of cognition: planning, monitoring, and evaluating were manifested by the students. Further, results from the paired sample t-test revealed that there was a significant change between the scores of the learners in pre-test and post-test, indicating that the MEMs have improved the conceptual understanding of students on the topic of cell cycle. Conversely, results from OLSES indicated that there was no significant change between the pre-intervention and post-intervention self-efficacy beliefs of the learners.